2013
DOI: 10.1007/s10897-013-9653-8
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Healthcare Providers’ Perspectives on the Implications of Genome‐Wide Testing in Pediatric Clinical Practice

Abstract: The utilization of genome-wide chromosomal microarray analysis (CMA) in pediatric clinical practice provides an opportunity to consider how genetic diagnostics is evolving, and to prepare for the clinical integration of genome-wide sequencing technologies. We conducted semi-structured interviews with 15 healthcare providers (7 genetic counselors, 4 medical geneticists, and 4 non-genetics providers) to investigate the impact of CMA on clinical practice, and implications for providers, patients and families. Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 52 publications
1
26
0
Order By: Relevance
“…Next‐generation sequencing offers knowledge but comes with challenges . Genome‐wide testing produces huge quantities of information, some of which may be uncertain and/or unanticipated, raising ethical concerns about disclosure and stimulating debate regarding how best to integrate such testing into prenatal clinical practice …”
Section: Introductionmentioning
confidence: 99%
“…Next‐generation sequencing offers knowledge but comes with challenges . Genome‐wide testing produces huge quantities of information, some of which may be uncertain and/or unanticipated, raising ethical concerns about disclosure and stimulating debate regarding how best to integrate such testing into prenatal clinical practice …”
Section: Introductionmentioning
confidence: 99%
“…VUS are relatively common findings, but there is little empiric data about the impact of receiving VUS results. Studies suggest that VUSs can cause concern for families if not expected or explained correctly [8688]. Reiff et al (2012) studied how families understand CMA results using semi-structured interviews with 31 parents of 25 pediatric outpatients who received either pathogenic (n=11) or VUS (n=14) results and found that incomplete comprehension (defined as an individual’s self-reported ability to grasp the meaning of the result) of test results and a need for more information to improve understanding of results were prominent issues for parents [86].…”
Section: Counseling Challenges Related To Genome-wide Genetic Testingmentioning
confidence: 99%
“…A survey of 40 physicians found that their comfort levels of explaining CMA results to families were lowest for VUS (score of 3.46 on a 6-point Likert scale with 6 being the highest comfort level) compared to a normal or abnormal result [87]. Physicians also felt that parents did not have a good understanding of CMA results (score of 2.49 on a 6-point Likert scale), despite families reporting a good understanding of CMA results in a prior study by the same group [8688]. …”
Section: Counseling Challenges Related To Genome-wide Genetic Testingmentioning
confidence: 99%
“…Experts including genetics researchers (Appelbaum et al, 2015; Kleiderman et al, 2015; Middleton et al, 2016; Rahimzadeh, Avard, Senecal, Knoppers, & Sinnett, 2015; Ramoni et al, 2013), genetics health professionals (Brandt et al, 2013; Grove, Wolpert, Cho, Lee, & Ormond, 2014; Lemke, Bick, Dimmock, Simpson, & Veith, 2013; Lohn et al, 2013; Middleton et al, 2016; Scheuner et al, 2015; Yu, Harrell, Jamal, Tabor, & Bamshad, 2014), healthcare providers (Reiff et al, 2014; Strong, Zusevics, Bick, & Veith, 2014), and advisory bodies (Fabsitz et al, 2010; Green et al, 2013; Weiner, 2014) have all weighed in with preferences and policy recommendations. These recommendations are varied and have generated much discussion, especially the American College of Medical Genetics and Genomics (ACMG) 2013 recommendation that a minimum list of 56 genetic results deemed medically actionable should always be returned, regardless of patient preference, age (including children), or age of onset (Green et al, 2013).…”
Section: Introductionmentioning
confidence: 99%